Extract of palm leaf and a composition comprising the same for increasing bone mineral density and arterial homeostasis - Mohamed, Suhaila; Baksh, Ahdab Abdul Razak; Jaffri, Juliana; Rohimi, Nordanial; Abdul Razak, Musyida; Ahmad, Intan Natasya; Anyanji, Victor Uchenna (2011)
The present invention discloses an extract of palm leaf and a composition containing the same as an effective ingredient for the prevention and treatment of osteoporosis. In an embodiment, the composition further includes a seaweed extract. The composition disclosed herein possesses synergistic activities of promoting bone mineral and/or calcium density, as well as arterial integrity and homeostasis in mammals, so that the composition can be effectively used for the prevention and treatment of osteoporosis.